Reauthorization of NCLB: Time to Reconsider the Scientifically Based Research Requirement - Suzanne Franco (Nonpartisan Education Review, 2007)
The federal initiative, NCLB, includes guidelines about educational research methodology as well as school practices ("No Child Left Behind Act," p. 532). The law states that reforms and school practices should be based on scientifically based research (SBR). SBR is mentioned over 100 times in NCLB (A. Smith, 2003, p. 126). Next to the strong emphasis on dis-aggregation of test scores, NCLB’s reference to SBR has spawned the next most frequent number of responses in the literature (Viadero, 2004). Educational researchers spend time “fighting these designs when they are inappropriate or irrelevant, which is often the case” (Eisenhart, 2005, p. 246).